(untitled) (European journal of volunteering and community-based projects, 2020)
The Legislative Decree 117/2017 changes the regulation of the third sector. On 05.03.2020 a special Ministerial Decree introduced the obligation of new reporting models that push third sector entities to provide evidence also to non-financial elements by identifying the most appropriate economic valuation. Despite these premises, the legislator has not yet offered any objective and certain assessment tools. This gap could be bridged by a social impact assessment (i.e. SIA theory). Through a qualitative approach, the authors provide evidence about the Turin Chamber of Commerce guidelines that aim to bridge this information gap while responding to the public’s need to detect the impact generated and the added value of limited public resources absorbed by the third sector. At the same time, social impact assessment could respond to the information asymmetry between organisations and funders by generating a virtuous relationship of mutual trust. Reflections on the evolution driven by the reform direct future research towards identifying new integrated models that should favour cost-effectiveness balances.